2020
DOI: 10.1111/1759-7714.13416
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and risk factors of drug‐induced lung injury by ALK tyrosine kinase inhibitors: A single center retrospective analysis

Abstract: Background: If anaplastic lymphoma kinase (ALK) gene rearrangement in lung cancer is identified, ALK-tyrosine kinase inhibitors (ALK-TKIs) can be an effective treatment. However, the details of drug-induced lung injury (DILI) caused by ALK-TKI, which can be a serious side effect of ALK-TKIs, remains unclear. This study aimed to investigate the clinical features and the onset risk factors of DILI by ALK-TKIs in clinical practice. Methods: The clinical features of 56 consecutive patients who received crizotinib,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Its molecular targeting, high specificity, targeted drugs, without blood and neurotoxicity and other characteristics, greatly improve the quality of life of patients [ 115 ]. Several clinical drugs have been developed [ 116 , 117 , 118 ], such as the inhibition of epidermal factor receptor (EGFR) [ 119 ], anaplastic lymphoma kinase (ALK) and ROS1, etc. Currently, several new treatment combinations and new drugs are being investigated.…”
Section: Resultsmentioning
confidence: 99%
“…Its molecular targeting, high specificity, targeted drugs, without blood and neurotoxicity and other characteristics, greatly improve the quality of life of patients [ 115 ]. Several clinical drugs have been developed [ 116 , 117 , 118 ], such as the inhibition of epidermal factor receptor (EGFR) [ 119 ], anaplastic lymphoma kinase (ALK) and ROS1, etc. Currently, several new treatment combinations and new drugs are being investigated.…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, the incidence of Interstitial lung disease (ILD) in Asian patients from the J-ALEX study was 8%, while in non-Asian patients from the ALEX study ILD was 1% [50,51]. The pattern of pulmonaryinvolvement, secondary to ALK-TKIs, is usually organized pneumonia with generally good response to corticosteroids [52]. The timing of toxicity presentation does not help in the differential diagnosis of COVID-19, as it can occur from a few days to several months after treatment initiation, with the exception of Brigatinib, for which some studies have reported few cases of early toxicity within the first 7 days of treatment [51][52][53].…”
Section: Treatment Related Adverse Effects Influence On Covid-19 Diagnosismentioning
confidence: 99%
“…The pattern of pulmonaryinvolvement, secondary to ALK-TKIs, is usually organized pneumonia with generally good response to corticosteroids [52]. The timing of toxicity presentation does not help in the differential diagnosis of COVID-19, as it can occur from a few days to several months after treatment initiation, with the exception of Brigatinib, for which some studies have reported few cases of early toxicity within the first 7 days of treatment [51][52][53]. ILD is more frequent in smokers and has been associated to renal function reduction, older age, and previous pleural effusion [54].…”
Section: Treatment Related Adverse Effects Influence On Covid-19 Diagnosismentioning
confidence: 99%
“…In addition, identifying speci c drugs with potential risks for each patient with DLI is also challenging. Previous studies have suggested that age, gender, smoking, pulmonary surgery, thoracic radiotherapy, chemotherapy, diabetes, hypoproteinemia, and pre-existing lung disease might be risk factors for DLI [7][8][9][10][11] . However, the information about DLI in clinical practice is still limited, and the clinical features and pathogenetic factors of DLI are not fully clear.…”
Section: Introductionmentioning
confidence: 99%